Estimation of Balance Reliability for Deficit Power System - O. I. Alexandrov; N. V. Radoman; T. E. Zhykovskaja (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents a method for complex estimation of balance reliability for a deficit power system. An integral estimation is based on a vector function of the total power shortfall. Its components are presented in the form of active power node capacities of different types and include generating, load nodes, and also nodes which are bound to intersystem transmission lines, including reversing ones.The task takes into account values of available reserve capacities and values of taken-out repair capacities including nodes used for binding to power-intensive industrial enterprises which carry out a consumer-regulator role.The search is carried out in the definition domain pertaining to multi-criteria complicated function which is created by a complex of regime, technical and cost limiting conditions. Conditions and stages of parameter correction for a scheduled  mode have been formulated in the paper.